Effectiveness of a community-based intervention for weight loss on cardiometabolic risk factors among overweight and obese women in a low socio-economic urban community: findings of the MyBFF@home - Ahmad Zamri, Liyana; Appannah, Geeta; Zahari Sham, Siti Yazmin; Mansor, Fazliana; Mohammad Nor, Noor Safiza; Ambak, Rashidah; Abdul Samad, Azah; Dahlan, Nofi Yuliani; Aris, Tahir (BioMed Central, 2018)
Background: The effectiveness of lifestyle intervention for weight loss on cardiometabolic risk factors among overweight and obese individuals in the community setting remains inconclusive. This study aimed to evaluate the effect of a 6-month weight loss lifestyle intervention on cardiometabolic risk factors among overweight and obese women and the sustainability of the changes in those markers at 12-month follow-up, comparing an intervention group with a control group. Methods: A total of 243 participants from MyBFF@home were included in this study. Fasting blood samples at baseline, 6- and 12-month were assessed for fasting plasma glucose (FPG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides. The effect of the intervention on cardiometabolic risk markers were investigated within and between study groups using t-test and general linear model (GLM) repeated measure ANOVA. Results: Results from repeated measures ANOVA showed intervention effect only in TC where significant reduction was found in the intervention group (- 0.26 mmol/L [95% CI: - 0.47 to - 0.06], p < 0.01) compared to the control group (- 0.06 mmol/L [95% CI: - 0.28 to 0.17]) at 12 months. At 6 months, TC was reduced significantly in both groups but only intervention group retained the reduction in maintenance phase while, the level increased significantly in the control group (0.22 mmol/L [95% CI: 0.06 to 0.38]). This attributed to significant increase in TC/HDL-C ratio in the control group during maintenance phase (0.32 [95% CI: 0.15 to 0.50], p < 0.001). The intervention group also showed trend of reduction in FPG at 6 months and further decreased during maintenance phase (- 0.19 mmol/L [95% CI: - 0.32 to - 0.06], p < 0.01). At 6 months HDL-C was maintained in the intervention group but reduced significantly in the control group (- 0.05 mmol/L [95% CI: - 0.10 to - 0.01], p < 0.05). No significant difference was detected in both markers when compared between groups. Conclusions: In the context of low socio-economic communities, this study supports that weight loss related lifestyle modifications over a 6-month period could improve selected cardiometabolic risk factors, particularly fasting glucose, TC and HDL-C in overweight and obese women with favourable sustainability over a 12-month period.